PENDEKATAN PETA KONSEP DALAM PEMBELAJARAN MATEMATIKA - Yoseph Pius Kurniawan Kelen (KH. A. Wahab Hasbullah University, 2015)
This research includes Classroom Action Research (CAR) with its phases: 1) Planning (Planning), 2) action (acting), 3) Observation (observasing), and 4) Reflection (reflecting) .. The data used in the study These are: data about the learning situation at the moment carried out actions that obtained by observation, and data on student learning outcomes obtained by giving the test to the students. The problem of how to approach this research concept maps in learning mathematics. The purpose of this study was to determine the increase achievement in math learning by using concept map approach. As a benefit of this research is the input material for teachers in mathematics learning activities with learning approach that is appropriate for each study topic. Analysis of the data using the formula of individual completeness and thoroughness class generates the percentage of completeness class first cycle was 68.18% and cycle II of 87.5%. Thus, it can be concluded that the application of the concept map learning approaches in mathematics learning can improve student achievement. Keywords: Mathematics Learning, Approach Concept Map